Answer:
A. 45
Step-by-step explanation:
The mean is the average of the data set.
(14+62+35+38+58+46+62)÷7=
(76+35+38+58+46+64)÷7=
(111+38+58+46+64)÷7=
(149+58+46+64)÷7=
(207+46+64)÷7=
(253+64)÷7=
317÷7=
45.285714285714285714285714285714≈45
Our answer that makes the most sense is A. 45
Answer: B is correct
Step-by-step explanation:
if you do 2 ÷ 5 you get 0.4. But that isn't an option. So, the only other possibility would be -2 ÷ 5 which gives us -0.4, and that makes sense.
I'm not the greatest at explaining this one but hopefully, this helps!
Let x be how many hot dogs person b ate
therefore, person a ate x+8 hotdogs
and person c ate x-10 hotdogs
they all ate 130 hotdogs in total so
x + x + 8 + x - 10 = 130
3x -2 = 130
3x = 132
x = 44
so person b ate 44 hotdogs
person a ate 8 more so 52 hotdogs
and person c ate 10 less than person b so 34 hotdogs
Answer:
A 1:6
Step-by-step explanation:
3:18 simply to 1:6
Answer:
no solution
Step-by-step explanation:
Given
3(x - 3) = 3x , that is
3x - 9 = 3x ( add 9 to both sides )
3x = 3x + 9 ( subtract 3x from both sides )
0 = 9 ← not possible
This indicates the equation has no solution